PTPTN waives slain policeman's loan - News Straits, Times (New Straits Times, 2013)
KANGAR: The National Higher Education Fund Corporation (PTPTN) has waived the payment of the remainder of the study loan of slain commando, Assistant Superintendent Zulkifli Mamat, which amounts to RM16,250.